E-201 Outcomes of flow diversion of middle and anterior cerebral aneurysms and the incidence of neo-intimal hyperplasia. (4th August 2020) - Kaur, G; Dakay, K; Gandhi, C; Al-Mufti, F; Santarelli, J
Abstract : Introduction: Flow diversion of distal aneurysms like the middle cerebral artery (MCA) and anterior cerebral artery (ACA) is a safe and effective treatment modality for wide necked aneurysms, not amenable to any other endovascular approach. We present our experience with flow diversion of distal vasculature and the outcomes. Materials and Methods: Distal aneurysms were defined as MCA and ACA aneurysms. All distal aneurysm treatments performed with a Pipeline embolization device (PED) from September 2017 to January 2020 were collected in a prospectively maintained database. Patient demographics, clinical, and angiographic outcomes including digital subtraction angiography were registered. 6 month follow up angiograms were performed when possible to look for resolution of the aneurysm and the incidence of neo-intimal hyperplasia. Results: A total of 36 distal aneurysms were treated by pipeline flow diversion, of which 19 were MCA aneurysms and the rest were ACA aneurysms. Mean age is 58± 11 years. 6 month follow up is available for 21 of the 36 treated cases, with 3 being lost to follow up and the rest awaiting 6 month follow ups. From the follow ups available (n=21), the incidence of complete aneurysmal resolution was 76% (16/21). Neo-intimal hyperplasia was seen in 52% (11/21), and all cases with intimal hyperplasia were asymptomatic and had complete aneurysmal resolution. All cases of neo-intimal hyperplasia were mild to moderate and were managed by continuing dual antiplatelet therapy for another 6 months. There were 2 complications in the entire cohort- 1 intracerebral hemorrhage and 1 groin pseudo-aneurysm. There was 1 asymptomatic pipeline occlusion with no clinical manifestations. Conclusion: In our experience, flow diversion of distal wide necked MCA and ACA aneurysms is a safe and effective treatment strategy. The presence of neo-intimal hyperplasia after flow diversion of distal aneurysms is a frequent finding at 6 month follow up angiography but has been clinically asymptomatic in all cases. Disclosures: G. Kaur: None. K. Dakay: None. C. Gandhi: None. F. Al-Mufti: None. J. Santarelli: None.